LEGAL AND REGULATORY ASPECTS OF THE USE OF NUCLEAR-PHYSICS RESEARCH IN FORENSIC EXPERT ACTIVITIES - Біленчук, Петро Дмитрович; Сватюк, Наталія Іванівна; Поп, Оксана Михайлівна; Симканич, Олеся Іванівна; Маслюк, Оксана Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: establishing legal and judicial capacity of identifying natural objects by nuclear-physical methods in forensic examination. Research methods: legal and rights issues of the possibility of using low-background nuclear-physical techniques to identify material but not radioactive objects, which can be evidence elements for forensic examination. The determination of the composition and certification of the studied objects in the process of forensic examination requires the development and implementation of a methodology for measuring their identification features. Nuclear methods are the basic research tool in nuclear forensic laboratories to answer a number of questions, in particular, on the chemical, impurity and isotopic composition, ratio of components, the presence and intensity of a-, b- or g- emitting nuclei of the objects of study. In methodological terms, this task is new for the needs of forensic expert assessments both when choosing technical means and regulations for working with natural objects of research. Result: the high reliability and objectivity of evidence for criminalistic practice, which can be obtained using these techniques, is shown. The important factors for the spatial localization of non-radioactive objects and environmental samples (soil, silt, rocks) are the content and ratio of daughter’s isotopes of natural U / Th series and nuclides of technogenic origin. The example of silt and rock of Transcarpathia illustrates the possibility of establishing standards for the content of the corresponding chemical elements for these objects and the possibility of their nuclear dating. This allows to identify environmental objects and make them tied to a specific territory, that is extremely important for forensic examination. Discussion: the feasibility of establishing a network of national nuclear forensic laboratories for expert research.